Proposal of a Ranking Method for Comments in Social Media Using Ratings of Comment Posters (Global Journal of Computer Science and Technology, 2013)
Many social media adopt a ranking method in which comments are ranked in the order of the number of ratings attached to each comment. However, this method has the disadvantage of ratings being concentrated on comments posted at an early stage. Even if there are high-quality comments posted later, most of them are buried without being noticed. This paper proposes a ranking method that considers not only the ratings for each comment but also the previous ratings the comment poster has received. The effectiveness of the proposed method is evaluated through a simulation. We demonstrate that with the proposed method, high-quality comments are displayed in the higher positions regardless of the posting period.
Keywords: ranking method; comment; social media; rating; comment poster